Pengaruh Brand Love terhadap Brand Loyalty dan Willingness to Pay Premium Price pada layanan streaming Netflix, Self Esteem sebagai Mediasi - Prasetya, Dimas Bagus; Prakosa, Muhammad Rizki Akbar; Nurdiansyah, Fadlan Hasan (Universitas Tanjungpura, 2025)
This study investigates the influence of Brand Love on Brand Loyalty and Willingness to Pay Premium Price in the context of Netflix’s streaming services, with Self Esteem examined as a mediating variable. The research aims to explain the psychological mechanisms that link emotional attachment to consumer loyalty and premium payment behavior. The study involved 171 Netflix users residing in Surakarta. Data were collected through an online survey using a structured questionnaire with a five-point Likert scale. The measurement of Brand Love, Self Esteem, Brand Loyalty, and Willingness to Pay Premium Price employed validated indicators from prior research. Data were analyzed using Structural Equation Modeling with the Partial Least Squares approach to assess measurement reliability and structural relationships. The findings show that Brand Love significantly influences Brand Loyalty and Willingness to Pay Premium Price. Brand Love, however, does not directly influence Self Esteem, while Self Esteem has a positive effect on Brand Loyalty. Brand Loyalty does not significantly affect Willingness to Pay Premium Price. The results highlight the importance of emotional attachment in shaping consumer behavior and suggest that psychological factors related to self-perception contribute to building long-term loyalty. These insights provide strategic implications for digital streaming platforms in strengthening consumer–brand relationships.